"A Family for Every Child": Discursive Constructions of "Ideal" Adoptive Families in Online Foster Adoption Photolistings That Promote Adoption of Children From Foster Care. Issue 1 (2nd January 2017) - Thomas, Lindsey J.; Scharp, Kristina M.
ABSTRACT: Despite documented cultural and institutional preferences for biological family ties, approximately 100, 000 children await adoption in the U.S. foster care system. Child welfare professionals have the important task of finding these children permanent families, yet little is known about this process or how "ideal" adoptive families are constructed. Thus, this study critically examines photolistings (N = 104) fromwww.afamilyforeverychild.org . Findings indicate that discursive constructions of "forever family, " based on chosen family structure and familial performance, counter biology-based understandings of family. Practical applications that might open untapped opportunities to connect children with permanent families are discussed.